2020
DOI: 10.1186/s12876-020-01460-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proton pump inhibitor use on the esophageal microbial community

Abstract: Background Changes in the esophageal microbiome correlate with esophageal disease, but the effects of proton pump inhibitor (PPI) drugs are incompletely characterized. Our objective was to identify the effects of PPI use on the microbial community of the esophagus. Methods Mucosal biopsies of the distal esophagus were analyzed using a customized esophageal microbiome qPCR panel array (EMB). Patient demographics, use of PPIs, duration of use and dose were recorded. Results Fifty-eight patients were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Gastrointestinal involvement was common (76%) in our cohort. There are case reports of MIS-C patients presenting with pain abdomen and diarrhoea, and then developing Kawasaki-like features including mucositis, and coronary artery dilatation [ 16 ]. Some patients have been admitted with a suspicion of appendicitis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal involvement was common (76%) in our cohort. There are case reports of MIS-C patients presenting with pain abdomen and diarrhoea, and then developing Kawasaki-like features including mucositis, and coronary artery dilatation [ 16 ]. Some patients have been admitted with a suspicion of appendicitis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Indian study of 32 patients, ventricular dysfunction was found in 13 patients; 11 had normal EF at 2 weeks follow up while rest 2 were also normal by 6 weeks [ 16 ]. Persistent abnormalities in strain and diastolic function in patients with MIS-C with normal EF have also been reported [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that there was no effect of PPI use on alpha and beta diversity of the esophageal microbiome in GERD and BE patients, but PPI use was associated with an increase in Firmicutes and a decrease in Bacteroidetes and Proteobacteria [ 160 ]. Tasnim et al used a custom quantitative PCR array to measure select microorganisms in biopsies from the distal esophagus to examine the effect of PPI use on the esophageal microbiome in 58 GERD patients (including 26 with BE), among which 52 were PPI users and 6 were nonusers [ 164 ]. The authors found that PPI users had significantly higher levels of Actinomyces ( p < 0.01) compared with nonusers, but there was no difference in the other organisms that were measured.…”
Section: Esophageal Microbiomementioning
confidence: 99%
“…However, the majority of patients in our study did use proton pump inhibitors. Additionally, a recent study by our investigative team showed that there were no differences in the esophageal microbiome in patients who did and did not use proton pump inhibitor medications [ 42 ].…”
Section: Discussionmentioning
confidence: 99%